Innate immunity and monocyte-macrophage activation in atherosclerosis - Davies Alun H; Falck-Hansen Mika A; Shalhoub Joseph; Monaco Claudia (BMC, 2011)
Abstract Innate inflammation is a hallmark of both experimental and human atherosclerosis. The predominant innate immune cell in the atherosclerotic plaque is the monocyte-macrophage. The behaviour of this cell type within the plaque is heterogeneous and depends on the recruitment of diverse monocyte subsets. Furthermore, the plaque microenvironment offers polarisation and activation signals which impact on phenotype. Microenvironmental signals are sensed through pattern recognition receptors, including toll-like and NOD-like receptors - the latter of which are components of the inflammasome - thus dictating macrophage behaviour and outcome in atherosclerosis. Recently cholesterol crystals and modified lipoproteins have been recognised as able to directly engage these pattern recognition receptors. The convergent role of such pathways in terms of macrophage activation is discussed in this review.